(untitled) (Web of Teachers: Inderscience Research, 2024)
The purpose of studying GLKs is to study them, so that humanity can understand dark matter, dark matter, matter around black holes, their properties. To find correlations between parameters and derive equations connecting them. The connection between the components of GraL J024848.7+191331, brightness curves, microlensing.